From Doubt to Confidence: Transformation of Belief in the Prayer of Prophet Yunus in Q. S. Anbiya’ Verse 87 as a Healing Media in Javanese Muslim Community - Sulistyorini, Khofifah Dwi (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the transformation of belief among Javanese Muslim communities regarding the prayer of Prophet Yunus in Q.S. al-Anbiya’ verse 87 as a medium of healing. The research uses a qualitative approach through library research supported by social phenomena within the community. The analysis applies the perspective of Peter L. Berger and a critical reading approach to understand the textual, implicit, and social meanings of the verse. The findings show that the prayer of Prophet Yunus is not only understood as a religious text, but also practiced as a symbol of hope and a spiritual healing medium, especially for non-medical illnesses. This belief is formed through experience, tradition, social interaction, and the influence of the religious culture of Javanese Muslim society, leading to a transformation from doubt to conviction. Thus, the prayer of Prophet Yunus becomes part of the Living Qur’an practice that functions as a medium for inner peace, spiritual strengthening, and healing efforts in community life.